2010
DOI: 10.1161/circulationaha.109.911339
|View full text |Cite
|
Sign up to set email alerts
|

Acute Cardiovascular Effects of Apelin in Humans

Abstract: Background-Apelin, the endogenous ligand for the novel G protein-coupled receptor APJ, has major cardiovascular effects in preclinical models. The study objectives were to establish the effects of acute apelin administration on peripheral, cardiac, and systemic hemodynamic variables in healthy volunteers and patients with heart failure. Methods and Results-Eighteen patients with New York Heart Association class II to III chronic heart failure, 6 patients undergoing diagnostic coronary angiography, and 26 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
170
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(188 citation statements)
references
References 34 publications
13
170
1
Order By: Relevance
“…Acute administration of apelin in people with heart failure induced an increase of coronary blood flow, decrease in blood pressure and increase in cardiac output 70 . Further studies demonstrated an increase in cardiac index and ejection fraction that remained increased during a six-hour infusion, but heart rate increase occurred only during the first hour of the infusion 71 .…”
Section: Apelinmentioning
confidence: 93%
“…Acute administration of apelin in people with heart failure induced an increase of coronary blood flow, decrease in blood pressure and increase in cardiac output 70 . Further studies demonstrated an increase in cardiac index and ejection fraction that remained increased during a six-hour infusion, but heart rate increase occurred only during the first hour of the infusion 71 .…”
Section: Apelinmentioning
confidence: 93%
“…Thus, our discovery of an apelin variant that uncouples cardiovascular from metabolic activity suggests the possibility of developing apelin peptides with the ability to treat metabolic disease without impacting cardiovascular function. In addition to lacking cardiovascular activity, such a candidate therapeutic would also need to exhibit a longer half-life than wild-type apelin-36 to allow for a once daily or less frequent dosing interval (15).…”
Section: Table 1 Properties Of Apelin Peptides and Variantsmentioning
confidence: 99%
“…These assumptions were made after observing the effects of experimental iv administration of apelin to animals and humans with heart failure: it acts as a potent inotrope and increases the contractility of the heart, the ejection fraction and the cardiac output and lowers the left ventricle diastolic pressure . These effects were described initially on isolated hearts on which apelin exerted a clear inotropic effect, especially on failing myocardium [23,24], and then were reproduced on healthy and heart failure human volunteers [25,26]. All these scientific results are proof of the beneficial role of apelin in the human body and in particular in the functioning of the cardiovascular system but it suggests its limited protective effect until it is overcome by the injurious molecular pathway and its tissular and serum level begin to fall.…”
Section: Introductionmentioning
confidence: 98%